Effect of Dietary Supplementation of Fenugreek Seed (Trigonella foenum) on Body Condition Score, Udder Health and Faecal Egg per Gram of Dairy Cows - Rathore, Neha; Mehta, Mukesh K.; Jain, Ravindra K.; Patil, Ashok K. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The study was carried out to observe the effect of dietary supplementation of Fenugreek seed on body condition score (BCS), udderhealth, and faecal egg per gram (EPG) of dairy cows. Twelve multiparous lactating cows at an early stage of lactation were selectedand randomly allotted into two groups (n=6) of six cows each. The animals in group-T0 were fed normal feed without fenugreek seedsand served as control. The animals in group-T1 were given ground fenugreek seeds (Trigonella foenum) @ 100 g/d/head for 90 days, inaddition to the usual feed/fodder. The udder health, body condition score, and faecal egg count of gastro-intestinal helminths wererecorded fortnightly for 90 days. The mean numerical value of BCS was higher (3.78 ± 0.06 vs. 3.60 ± 0.07), whereas milk pH (6.63 ±0.02 vs. 6.81 ± 0.02), SCC (1.95 ± 0.07 vs. 2.37 ± 0.05 x105) and EPG (866.67 ± 21.40 vs. 964.29 ± 27.29) were non-significantly lower intreatment group as compared to the control group.
Keywords: Dairy cows; Fenugreek seed; , Gastro-intestinal helminths; Milk pH; Somatic cell count; Udder health